Penerapan Manajemen Risiko Berbasis ISO pada UMKM Jasa Penjahitan Pakaian: Studi Kasus Umi Tailor - Amelia, Yesi; Kartini, Tini; Mahmudin, Anggi; Alfiana, Alfiana (Indo Publishing, 2026)
This study aims to analyze the implementation of risk management based on ISO 31000:2018 in Umi Tailor, a micro, small, and medium enterprise (MSME) operating in the clothing tailoring service sector, to enhance business sustainability and service quality. This research employs a qualitative descriptive approach with a case study method, using in-depth interviews, field observations, and documentation studies as data collection techniques. The risk management process is conducted systematically through risk identification, analysis, evaluation, and risk treatment in accordance with the ISO 31000 framework. The results indicate that Umi Tailor faces various risks originating from production, marketing, financial, human resources, and legal aspects. High and very high risk levels are mainly associated with unstable cash flow, dependence on a single skilled tailor, rising raw material prices, work fatigue, and limited production capacity. The application of ISO 31000 enables the enterprise to prioritize risks and develop practical mitigation strategies suited to MSME capabilities, such as establishing standard operating procedures, strengthening digital financial records, regulating working hours, and optimizing digital marketing. This study is expected to serve as a practical reference for tailoring service MSMEs in implementing effective and scalable risk management practices.